2020
DOI: 10.1029/2019wr026948
|View full text |Cite
|
Sign up to set email alerts
|

Drought‐Induced Soil Desiccation Cracking Behavior With Consideration of Basal Friction and Layer Thickness

Abstract: Drought‐induced cracking of soils is of great concern with the advent of global climate change. The cracking process accelerates the evaporation rate of pore water, lowers the water retention capacity, and degrades the hydraulic‐mechanical properties of soils. Basal friction and layer thickness are two important aspects affecting the subsurface cracking. To explore their detailed effects on soils under drying, we conduct a series of desiccation tests on twelve slurry soil bars and select four types of base mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 83 publications
(175 reference statements)
0
22
0
Order By: Relevance
“…The modellings revealed that individual crack propagation depends on the stress/strain concentration in local soil bodies (Lin et al., 2021; Pouya et al., 2019; Sánchez et al., 2014). This outcome was further confirmed in soil desiccation experiments at the laboratory scale, where the progression of individual crack branches was traced using precise image analysis techniques such as Digital Image Correlation (DIC) and Particle Image Velocimetry (PIV) (Li et al., 2019; Trabelsi et al., 2018; Wang et al., 2018; Wei et al., 2016; Zeng et al., 2020). It should be pointed out that the hydro‐mechanical coupled process along soil desiccation cracking is complicated, considering the interaction among pore water evaporation and migration, solid particle motion and internal stress evolution (Chertkov & Ravina, 2001, 2002; Costa et al., 2013; Kodikara & Costa, 2013; Li et al., 2011, 2019; Lin et al., 2021; Péron et al., 2009; Pouya et al., 2019; Sánchez et al., 2014; Shin & Santamarina, 2011; Shorlin et al., 2000; Toga & Alaca, 2006).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The modellings revealed that individual crack propagation depends on the stress/strain concentration in local soil bodies (Lin et al., 2021; Pouya et al., 2019; Sánchez et al., 2014). This outcome was further confirmed in soil desiccation experiments at the laboratory scale, where the progression of individual crack branches was traced using precise image analysis techniques such as Digital Image Correlation (DIC) and Particle Image Velocimetry (PIV) (Li et al., 2019; Trabelsi et al., 2018; Wang et al., 2018; Wei et al., 2016; Zeng et al., 2020). It should be pointed out that the hydro‐mechanical coupled process along soil desiccation cracking is complicated, considering the interaction among pore water evaporation and migration, solid particle motion and internal stress evolution (Chertkov & Ravina, 2001, 2002; Costa et al., 2013; Kodikara & Costa, 2013; Li et al., 2011, 2019; Lin et al., 2021; Péron et al., 2009; Pouya et al., 2019; Sánchez et al., 2014; Shin & Santamarina, 2011; Shorlin et al., 2000; Toga & Alaca, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…Consequently, there are limitations in understanding how internal cracks develop inside the entire soil, using the infrared thermal imaging technique only. For example, Zeng et al (2020) highlighted that the boundary effect between horizontal soil layers along the vertical direction could mobilize many cracks forming at the bottom of the overlying soil under evaporation and progressing toward the surface. To monitor the development of these cracks and understand their governing mechanisms, investigations need to apply other methods such as noninvasive techniques (e.g., X-ray CT) or embedded sensing elements in soils (e.g., distributed optical fiber sensing technique).…”
Section: Advantages and Limitationsmentioning
confidence: 99%
“…The water evaporation process during drying can be divided into three stages (Tang, Shi, et al., 2011; Zeng et al., 2020). In the first stage, the sample stays saturated with a constant evaporation rate and most of the cracks initiate during this stage.…”
Section: Description Of Numerical Modelmentioning
confidence: 99%
“…With the rapid development of computer imagery, digital image processing technology has been widely used in many fields in science and engineering. In studying the process of fracture development, it is necessary to process digital images quantitatively by calculating various fracture parameters in order to analyze the geometric and morphological characteristics of the fracture network [26][27][28]. In processing digital images, the first step is to convert the original colored image (Figure 3(a)) to grayscale in order to better observe the cracks (Figure 3(b)).…”
Section: Image Processingmentioning
confidence: 99%